Middle Eocene deformation and sedimentation in the Puna–Eastern Cordillera transition (23°–26°S): Control by preexisting heterogeneities on the pattern of initial Andean shortening - Hongn, Fernando Daniel (2007)
The Quebrada de los Colorados Formation, at the north end of Calchaquí Valley in Salta Province, northwest Argentina, preserves evidence of syndepositional deformation since the middle Eocene (ca. 40 Ma) that includes (1) an angular unconformity with the under- ying Salta Group (Paleogene), and (2) internal unconformities and changes in vertical facies succession and provenance. Its fossil record [mammalian (notoungulates), middle Eocene] is correlatable to the Casa Grande Formation, which also unconformably overlies the Salta Group; both units record middle Eocene deformation along the eastern border of the Puna Plateau and outline previous fi rst-order mechanical heterogeneities related to the Cretaceous rift basin border. Along the western margin of the Puna, Eocene deformation coincides with ther- mal (magmatic arc) and mechanical (basin inversion) heterogeneities. Thus, the distribution of Eocene deformation followed an irregular pat- tern as a consequence of the heritage of preexisting heterogeneities. Keywords: Eocene deformation, initial foreland, preexisting hetero- geneities, Central Andes.